Awareness, Access, and Use of Electronic Information Resources among the Seminarians in Nigeria. Issue 1 (2nd April 2016) - Adeyoyin, Samuel Olu; Idowu, Taiwo A.; Sowole, Adeniyi O.
Abstract: The advent of electronic information resources (EIR) has helped to break physical territorial boundaries and time to information accessibility. This has facilitated the utilization of information as a strategic tool and commodity for development all over the world. This study focused on awareness, access, and use of EIR among seminarians. A descriptive research design using the survey method was adopted for this study. A questionnaire was designed and used as the survey instrument. The population was made up of 140 seminarians randomly selected from the sampled institution. This study finds that the seminarians were fully aware of EIR, they have unrestricted access to EIR (except the very expensive and sophisticated ones), and they make use of them. EIR help seminarians in carrying out their course assignments, broaden their knowledge of the subject, and expose them to other peoples' ideas, opinions, and views. The findings further show that EIR provide an avalanche of information in a single medium, and such resources are convenient and easy to use. Lack of adequate knowledge of EIR hardware operations, financial capacity to acquire EIR gadgets or tools, erratic power supply, safety of EIR gadgets, and lack of adequate knowledge of different application software were considered by the seminarians as some of the challenges of EIR usage.